110k views
0 votes
Which value of y forms the solution of the system defined by y = 11x + 1 and 11x + 12y = 12? A. 1 B. C. 11 D.

User Basbabybel
by
5.5k points

2 Answers

3 votes

Answer: 1

Step-by-step explanation:

y = 11 x + 1

11 x + 12 y = 12

----------------------

11 x + 12 * ( 11 x + 1 ) = 12

11 x + 132 x + 12 = 12

143 x + 12 - 12 = 12 - 12

143 x = 0

x = 0

y = 11 * 0 + 1

y = 0 + 1

User Olivier Lasne
by
6.1k points
4 votes

A

given the 2 equations

y = 11x + 1 → (1)

11x + 12y = 12 → (2)

substitute y = 11x + 1 into (2)

11x + 12(11x + 1) = 12

11x + 132x + 12 = 12

143x + 12 = 12 ( subtract 12 from both sides )

143x = 0 ⇒ x = 0

substitute x = 0 into (1)

y = 0 + 1 = 1

the required value is y = 1 → A


User Lesque
by
6.6k points